China's Path towards Global Green Governance on Rare Earth Elements: Challenges and Opportunities: Aspirasi Tiongkok Menuju Pemerintahan Hijau Sedunia di Sektor Unsur Tanah Jarang: Tantangan dan Kesempatan - Joshua Gerry Mangkubudi; Triesanto Romulo Simanjuntak (Journal of Islamic World and Politics, 2023)
In light of surging demands for critical minerals and its rising profile as a global provider, China can no longer dismiss the negative ecological externalities resulting from its unregulated, near-monopoly production of rare earth elements (REE) since the 1970s. REE, consisting of 17 elements with naturally enhanced chemical properties, is critical for manufacturing future green infrastructures and technologies. However, the extraction and refining processes are resource-intensive and toxic to the immediate environment, further exacerbated by improper radioactive waste management, underfunded land restoration, and illegal mining. By extension, China’s supply supremacy came at the cost of socio-ecological deprivation disproportionately experienced by the local community compared to the beneficiary beyond borders. This study aims to assess the challenges and opportunities for China as they seek global leadership in green governance through its post-reform sustainable development model guided by Ecological Civilization (EC) principle. Using narrative analysis methods, we seek to assess the intersection among three threads: the historical account of China’s REE global dominance, their elite-based approach to governance, and the unmitigated socio-ecological impacts on the local community; regarding EC and its derivatives. While domestic consolidation is strategically integral to China’s EC-guided development agenda, it poses dormant risks of supply volatility for international markets, and innovative secondary production becomes the new source of competitive edge for supply diversification and norm-making power.